Генеральне консульство Грузинської Демократичної Республіки в Одесі у 1918-1921 рр.: напрями діяльності, постаті, значення - Музичко, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
Метою цієї статті є висвітлення діяльності в Одесі консульства
Грузії упродовж 1918–1921 рр. на підставі методології позитивізму. Ця
тема вперше ретельно висвітлена нами в історіографії. У результаті
дослідження зроблено такі висновки: 1) заснування Грузинського консульства в Одесі зумовлено тривалим процесом існування грузинської
громади у цьому місті; 2) в існуванні консульства спостерігаються
етапи: вересень 1918 — березень 1919 рр. — налагодження роботи консульства, перевага діяльності, спрямованої на транспортне посередництво колишнім солдатам і біженцям та економічне співробітництво;
березень–серпень 1919 р. — діяльність в екстремальних умовах комуністичного терору, допомога ув’язненим; вересень 1919 р. — січень 1920 р. — перерва в існуванні консульства, що було закрито прихильниками відновлення Російської імперії; січень 1920 — лютий 1921 р. — робота в Одесі «Особливої економічної місії Грузинської демократичної республіки на
Півдні Росії та в Румунії», що фактично було формою діяльності відновленого консульства. The purpose of this paper is to study the activities of the Georgian
Consulate in Odessa (1918–1921), based on positivism methodology. This
theme is carefully illuminated by us for the first time in historiography. The
study made the following conclusions: 1) the foundation of the Georgian
Consulate in Odessa was due to the long process of existence of the Georgian
community in this city; 2) there were stages in the existence of the Consulate :
September 1918 — March 1919 — the establishment of the Consulate, mainly
for activities aimed at the transport intermediation for former soldiers and
refugees, and economic cooperation; March–August 1919 — the activity in
extreme conditions of Communist terror, and assistance to inmates; September
1919 — January 1920 — a break in the existence of the Consulate, which was
closed by supporters of the Russian Empire restoration; January 1920 —
February 1921 — activity in Odessa of “the Special economic mission of the
Georgian democratic Republic”, which was actually a form of activity of
recovered Consulat. The Georgian Consulate in 1918–1921 in Odessa laid a
solid ideological Foundation for the modern phenomenon — the establishment
in 1998 of the Consulate General of Georgia in Odessa, which still operates
today. Further Studios of this theme must be unfolded in the direction of
expansion of the source base, study of Russian and Georgian archives, private
family collections, which primarily should contain valuable sources for
additional disclosure of the topic. The practical significance of the results
achieved lies in the fact that the study can be used for the contemporary
diplomatic service of Ukraine and Georgia, the formation of the policy of
historical memory, with the aim of honoring anniversaries of events related to
important aspects of the Georgian Consulate’s activity in Odessa.